Thoracic esophageal obstruction and its retrieval by rumenotomy in a graded Murrah buffalo calf - Pentyala, Vidya Sagar; Raghunath, Mullinti; Vaddi, Karunasri; Afreen, Fatheesha; Sreenu, Makkena (Buffalo Bulletin, 2020)
The report describes the diagnosis, treatment and outcome of the thoracic esophageal obstruction cranial to the cardia in and one month old, female graded Murrah buffalo calf.